Enhancing pain control in elbow rehabilitation; A case report of variable ropivacaine dosages through Brachial Plexus Catheter - Raj Khatiwada, Saurav; Sharma, Apurb; Raj Bhattarai, Prajjwal; Adhikari, Hemant; Khadka, Bikash (Birat Journal of Health Sciences, 2024)
Managing postoperative pain and discomfort during physiotherapy for upper arm injuries, including complex fractures or traumatic amputations, is crucial. Challenges include severe pain, stiffness, and limited range of motion. Physiotherapy is vital for preventing muscle atrophy, promoting joint mobility, and facilitating functional recovery. The successful management of postoperative pain and pain during physiotherapy in a 27-year-old female, who sustained multiple injuries including a displaced distal humerus fracture and a traumatic right-hand amputation, was achieved through the utilization of a continuous brachial plexus block with variable doses of ropivacaine. The patient’s history revealed a complex array of injuries, including a displaced distal humerus fracture and traumatic right-hand amputation, necessitating open reduction and internal fixation for the fracture and subsequent hand debridement. Despite addressing stiffness through capsulectomy, persistent concerns arose regarding postoperative pain and discomfort during physiotherapy sessions. To address these concerns, a continuous supraclavicular catheter was placed under ultrasound guidance, providing effective pain relief and facilitating physiotherapy interventions for optimal recovery. The patient underwent open reduction and internal fixation for the humerus fracture which was subsequently managed with amputation of several fingers and a hand debridement procedure. Following the surgeries, the patient complained of a stiff elbow, which was addressed through capsulectomy. However, concerns persisted regarding postoperative pain and pain during physiotherapy sessions, leading to the decision to place a continuous supraclavicular catheter. The catheter was accurately positioned under ultrasound guidance and tunneled under the skin, providing effective pain relief for seven days. Ropivacaine was administered as per the patient’s requirements, with a background infusion of 0.2% ropivacaine at 8-hour intervals, a 10 ml bolus of 0.2% ropivacaine administered half an hour before physiotherapy, and 10 ml of 0.5% ropivacaine during physiotherapy sessions if pain levels exceeded 4 on the numerical rating scale. This case highlights the utility of continuous brachial plexus blockade for prolonged postoperative analgesia and pain management during physiotherapy in patients with upper extremity injuries.